Perilaku Prososial Ditinjau dari Empati dan Kematangan Emosi - Gusti Yuli Asih; Margaretha Maria Shinta Pratiwi (Universitas Muria Kudus, 2010)
This recearched was aimed to realize the relation between empathy and emotional maturity toward prosocial behavior. There were two hypotheses proposed, which, there was a relationship existed between empathy and emotional maturity. Second hypothesis, there was a difference prosocial behavior among man and woman.Indicator used for measuring prosocial behavior, empathy, and emotional maturity was the use of scale. Subjects used in this research are 49 subjects. Data analysis used regression and t-test analysis. The result of the test showed that there was a significant positive relationship between empathy, emotional maturity, toward prosocial behavior showed by Rxy=0,932 with p=0,000, and no difference in prosocial behavior among men and women.